Brain Lateralization and Strategies to Improve Metalinguistic Ability in Arabic Language Acquisition - Ahmad Habibi Syahid; Talqis Nurdianto (Universitas Pendidikan Indonesia (UPI), 2022)
The study of language acquisition is still fascinating to study. A theory explains that language is Tauqify. The debate between the idea that explains that language ability is tabula rasa and language ability is a gift is a theory in language learning. This study aims to that there is brain lateralization based on theoretical data. Furthermore, there are strategies to improve metalinguistic ability in Arabic language acquisition. The method used in this study is a qualitative method with descriptive analysis. Researchers found five hypotheses about brain lateralization in second language acquisition in this study. First, the balanced bilingualism hypothesis. Second, the second language hypothesis. Third, the second language acquisition rate hypothesis. Fourth, the second language acquisition method hypothesis. Fifth, age hypothesis in second language acquisition. And there is more strategy to develop metalinguistic ability in Arabic language acquisition.